Oral health status in relation to nutritional status among institutionalized and non-institutionalized orphans in Baghdad city - Abdul Majeed, Aseel M; Al Dahan, Zainab A (Journal of Baghdad College of Dentistry, 2017)
Background: Nutritional condition was reported as one of the factors affecting the oral health status, particularly among underprivileged groups. Orphans are one of the known high-risk groups. The aims of this study were to assess the nutritional status of orphans, and its impact on the oral health status. Materials and Methods: Five-hundred children aged 6-12 years old, 254 males and 246 females: institutionalized, non-institutionalized orphans and controls were participated in this study. Nutritional status assessed according to body mass index (BMI). Ramfjord index teeth were examined to assess oral cleanliness and gingival condition. All data were analyzed using SPSS version 23. Results this study revealed the institutionalized orphans with low mean value of BMI, significant differ than non-institutionalized orphans and highly significant than controls, whereas the non-institutionalized orphans was significantly differ than controls. Each of institutionalized and non-institutionalized orphans was with highly significant elevated mean plaque and gingival indices than control, while significant high mean rank calculus index for non-institutionalized orphans than each of institutionalized orphans and controls was found. According to BMI indicators of both orphan groups, it was found that thinness group among institutionalized orphans with significant elevated Mean Plaque Index; however, high non-significant values for Gingival and Calculus indices were found among thinness grades. Conclusion: This study reflected that nutritional status is a relative factor; may affect the oral cleanliness and gingival health. Moreover, oral hygiene and preventive care are mandatory, should be stressed through dental care programs